A Qualitative Investigation of the Factors that Enhance, Impede, and Require Attention for the School Success and Engagement of At-Risk Newcomer Students - Elia, Julien; Cohen, Julie; Kassan, Anusha; Ngo, Hieu; Stevens, Kelli; Marulanda, David (Alberta Journal of Educational Research, 2022)
Little is known about best practices to support newcomer students with a history of emotional, behavioral, or learning challenges in their pursuit of school success and engagement. The Enhanced Critical Incident Technique was employed to explore the helping, hindering, and desired practices among nine teachers who have successfully supported at-risk newcomer youth in their educational pursuits in Canada. Results revealed 64 helping and 43 hindering factors as well as 27 wish list items related to participants’ experiences of supporting newcomer students in their school success and engagement. Recommendations are made at three levels: individual, curricula, and systemic. Keywords: newcomer youth, school disengagement, school re-engagement, academic success, qualitative research, enhanced critical incident technique On sait peu de choses sur les meilleures pratiques pour soutenir les élèves nouvellement arrivés et ayant des antécédents de problèmes émotionnels, comportementaux ou d'apprentissage dans leur quête de réussite et d'engagement scolaires. La méthode améliorée des incidents critiques a été utilisée pour explorer les pratiques positives, négatives et désirées chez neuf enseignants qui ont soutenu avec succès des jeunes nouveaux arrivants à risque dans leur parcours scolaire au Canada. Les résultats ont révélé 64 facteurs positifs et 43 facteurs négatifs ainsi que 27 éléments désirés liés aux expériences des participants en matière de soutien aux élèves nouvellement arrivés dans leur réussite scolaire et leur engagement. Des recommandations sont formulées à trois niveaux : individuel, curriculaire et systémique. Mots clés : jeunes nouveaux arrivants, désengagement scolaire, réengagement scolaire, réussite scolaire, recherche qualitative, méthode améliorée des incidents critiques